2016
DOI: 10.15740/has/fsrj/7.2/340-344
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietary micronutrient deficiency among adolescent girls

Abstract: Micronutrients such as vitamins and minerals play an important role in the promotion of health and prevention of disease. Adolescents are considered to be nutritionally vulnerable segment of the population. The present research study aims to assess the micronutrient deficiency in the diet of adolescent girls. For this purpose, 120 school going adolescent girls in the age range of 13-18 years were selected from the Udaipur city of Rajasthan. The 24-hours dietary recall method was used to collect the data. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…RDA) was only 10 and seven per cent for normal and thin adolescents, respectively, indicating around 90 and three per cent inadequacy of intake. Similar findings from Rajasthan 20 and Maharashtra 21 were also reported (30-70%). In this study, higher probability of dietary zinc inadequacy was observed in adolescents boys, which could be attributed to their higher requirement of zinc for growth.…”
Section: Discussionsupporting
confidence: 87%
“…RDA) was only 10 and seven per cent for normal and thin adolescents, respectively, indicating around 90 and three per cent inadequacy of intake. Similar findings from Rajasthan 20 and Maharashtra 21 were also reported (30-70%). In this study, higher probability of dietary zinc inadequacy was observed in adolescents boys, which could be attributed to their higher requirement of zinc for growth.…”
Section: Discussionsupporting
confidence: 87%